Comparison of Xiphophorus and human melanoma transcriptomes reveals conserved pathway interactions. (29th January 2018) - Lu, Yuan; Boswell, Mikki; Boswell, William; Kneitz, Susanne; Hausmann, Michael; Klotz, Barbara; Regneri, Janine; Savage, Markita; Amores, Angel; Postlethwait, John; Warren, Wesley; Schartl, Manfred; et al.
Summary: Comparative analysis of human and animal model melanomas can uncover conserved pathways and genetic changes that are relevant for the biology of cancer cells. Spontaneous melanoma in Xiphophorus interspecies backcross hybrid progeny may be informative in identifying genes and functional pathways that are similarly related to melanoma development in all vertebrates, including humans. To assess functional pathways involved in the Xiphophorus melanoma, we performed gene expression profiling of the melanomas produced in interspecies BC1 and successive backcross generations (i.e., BC5 ) of the cross: X. hellerii  × [ X. maculatus Jp 163 A ×  X. hellerii ]. Using RNA‐Seq, we identified genes that are transcriptionally co‐expressed with the driver oncogene, xmrk . We determined functional pathways in the fish melanoma that are also present in human melanoma cohorts that may be related to dedifferentiation based on the expression levels of pigmentation genes. Shared pathways between human and Xiphophorus melanomas are related to inflammation, cell migration, cell proliferation, pigmentation, cancer development, and metastasis. Our results suggest xmrk co‐expressed genes are associated with dedifferentiation and highlight these signaling pathways as playing important roles in melanomagenesis.